Fluidized Bed Drying of High Moisture Paddy in Two Stages - Thakur, A K; Gupta, A K (Journal of Agricultural Engineering, 2007)
Experimental investigations were carried for the determination of suitable rest duration and the stage; at which resting will provide better re-distribution of internal moisture in paddy grains subjected to fluidized bed drying. Incipient velocity was evaluated considering the drying conditions and the characteristics of the high moisture paddy. Intervening rest duration between first and second stage of drying; enhanced drying rate, reduced energy consumption and improved head rice yield. Single term diffusion based exponential model equation for infinite cylinder suitably fitted to first, rest and second stage drying data hy applying non-linear regression procedure. Analysis of the moisture loss values during rest stages and the diffusivity values of the second stage drying suggested that the intervening rest should be given at a moisture ratio around 0.712 for a period of approximately 90 min for adequate redistribution of internal moisture during rest duration. Energy requirement can be significantly saved (9-58%) by providing rest durations (30-120 min) in comparison to the continuous drying. Rest stage did not give significant effect on head rice yield while rest durations had a significant effect. Rest duration of 120 min considerably improved the head rice yield when compared from the results of continuous drying.